Anaerobic co-digestion of coffee waste with other organic substrates: A mixture experimental design. (June 2022) - Kampioti, Anastasia; Komilis, Dimitrios
Abstract: The viability of the anaerobic co-digestion of coffee waste (CFW) with other organic waste (cow manure-CM, food waste-FW, anaerobic sludge-AS) was investigated through measurements of biogas generation of various mixtures of the above substrates. The experiments were designed following the principles of mixture experimental design. Four different mixtures were tested anaerobically at 37 °C in 500 mL and 1 L anaerobic vessels. AS was used in some mixtures as an inoculum. The results were fitted to two empirical models in which biogas generation was the dependent variable and the fractions of the components in the mixture were the independent variables. According to the empirical models, the co-digestion of CFW with AS appeared to have a positive (synergistic) effect, generating 201 mL g −1 VSmixture, which was 12% higher than the amount generated from the mono-digestion of AS (179 mL g −1 VS). On the other hand, the co-digestion of CFW with CM and of CFW with FW had a negative (antagonistic) effect on biogas generation indicating that CFW inhibits biogas generation when mixed with CM and FW. Although the mono-digestion of CM resulted in an average of 149 mL g −1 VS of biogas, when CM was combined with CFW in a mixture, biogas generation was highly reduced by 43.8%–85.1%, depending on the CFW content of the mixtures, which was 25% and 50%, respectively. When co-digesting CFW with FW, the biogas generated was 7.02 mL g −1 VS that was obtained only from the FW in the mixture. Graphical abstract: Image 1 Highlights: The viability of co-digesting coffee waste (CFW) with other substrates was studied. A mixture experimental design approach was implemented. A small enhancement of biogas yield was observed when CFW was mixed with sludge. Digestion of cow manure and food waste was inhibited by the addition of CFW. Coffee waste is not recommended for use as a co-substrate in anaerobic treatment.